Conceptual Difficulties Experienced by First-Year Undergraduate Chemistry Students in Assigning Oxidation Number: A Case Study of High School Chemistry Textbooks - Rahmat Basuki (Universitas Gadjah Mada, 2020)
The purpose of this research was to investigate first-year undergraduate chemistry students’ understanding in assigning oxidation number following a case-study course instruction. A list of multiple choice question and interview section was formulated to identify the initial knowledge as representative of their conceptual understanding in assigning oxidation number obtained from their chemistry textbooks. This study revealed that most of 34 students who participated were confused about the nature of oxidation number. In the section of the interview which focused on applying “The Rules”, many students experienced more problems in assigning oxidation number of sulfur in S2O32– ion. Several misconceptions relating to the inappropriate assumption in assigning oxidation number were identified. The data illustrated how students attempt to make sense of the concept obtained from High School with the knowledge they had already constructed in solve of a given question. The research implied that the teachers, lecturers, curriculum developers, and High School Chemistry textbooks authors need to be cognizant of the importance of related concept (electronegativity and dot-Lewis structure) with oxidation number. The high school and chemistry textbook authors were recommended to introduce this interconnection (including formal charge) to minimize the misconception and conceptual difficulties experienced by first-year undergraduate chemistry students in assigning oxidation number.